Women's health care: The potential of long-chain Omega-3 polyunsaturated fatty acids - Hunt, W.; McManus, Alexandra (OA Publishing London, 2014)
Health care requirements are challenged by longer life expectancies with the fastest growing age group being women aged 85 years and older. The health care requirements for older women require further investigation with clinical trials seeking to represent this growing proportion of our population. Gender specific and general health care requirements for women over their lifespan need to be aimed at prolonging health adjusted life expectancy. Health care utilization has been linked to exposure to printed and online health information although which is the causal factor is unknown. Health literacy remains a concern in the transmission of health information especially with regard to complex messages such as the many health benefits associated with marine sourced long-chain omega-3 polyunsaturated fatty acids. These health benefits include: all-cause morbidity, coronary heart disease, cardiovascular disease, mental health including depression, dementia and Alzheimer’s disease, polycystic ovarian syndrome, dysmenorrhea and infant cognitive development. In many cases prevention is possible or at the very least a delay in onset of disease. Depression remains the single greatest contributor to the burden of disease in women in low-, medium- and high-income countries. Quality of womens’ health care throughout the lifespan and targeted health communications including those around diet has the ability to greatly influence health adjusted life expectancy.